Modernizing Islamic Education Curriculum to Align with the Digital Age: A Holistic Approach - Muhsin Muhsin; Afandi Afandi; Joni Indra Wandi; Asmaul Hikmatan; Amie Primarni (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2026)
The purpose of this research is to examine strategies for modernizing the Islamic education curriculum so that it aligns with the needs and challenges of the digital age. This study employs a qualitative descriptive-analytical method based on literature review, analysis of policy documents, and case studies of Islamic education institutions that have integrated digital technology into their curricula. The findings show that curriculum modernization in Islamic education is most effective when it adopts a holistic framework that simultaneously strengthens spiritual development, intellectual growth, and digital competence. The results indicate that integrating digital literacy with religious knowledge, applying student-centered learning, and utilizing innovative digital pedagogy can increase student engagement and protect learners from misinformation in online religious content, while still preserving teacher authority and core Islamic values. The study also finds that modernization helps Islamic education remain relevant to students’ daily digital experiences and supports their readiness for the contemporary labor market. In conclusion, modernizing the Islamic education curriculum is not a rejection of tradition but a necessary effort to reinterpret and implement Islamic teachings in a digital context, so that Islamic education remains relevant, inclusive, and transformative for learners in the modern era.